Image Segmentation Based on Color Dissimilarity - Karma, I Gede Made; Darma Putra, I Ketut Gede; Sudarma, Made; Linawati, Linawati (Informatica, 2022)
This study aims to develop a segmentation technique that can be used to identify objects in an image. The concept used is to imitate the human concept of recognizing an object based on its color difference. A color is considered different if it has different R, G or B values. Humans can only distinguish two colors clearly if they both have a DeltaE value of at least 8. The difference in DeltaE values is obtained from differences in the values of R, G or B, either alone or in pairs. The application of this concept to the segmentation technique has shown good results. This technique is able to give the same results and is good for images with JPG, PNG and BMP file types. The results of this segmentation will be very suitable for the process of identifying objects in an image.